Strategy of Loyalism: A Case Study of Syed Ahmad Khan’s Relations with the British - Farooq Ahmad Dar (Journal of Political Studies, 2020)
Syed Ahmad Khan is considered as a symbol of change. He achieved personal success and had contributed massively towards the development and progress of the Muslims of South Asia. He challenged traditional trends and showed a new path of modernity, through western education, to his community. However, in order to do so, he established friendly relations with the colonial masters, showed them his loyalty and pursued them for support. This paper is an attempt to find out that how much the British patronage helped Syed in achieving his goal and what was the impact of the strategy, he adopted.